Sekali lagi!= just one more! / Tracey Corderoy ; ilustrasi Alison Edqson ; penerjemah Grace ; editor Edith Natasha, Windrati Hapsari. - CORDEROY, Tracey; Edqson, Alison; Grace; Edith Natasha; Windrati Hapsari (Erlangga, 2015)
[24] hlm. : ilus. ; 22 cm [3 eks.]